Perubahan Kadar Hormon Tiroid pada Penderita Sindroma Nefrotik - Asripurwanti Asripurwanti; Samad Samad,; Lydia Koesnadi; W. Rochmanaji; Rudy Susanto (MEDIA MEDIKA INDONESIANA, 2008)
Thyroid hormones levels in nephrotic syndromeBackground: Nephrotic syndrome is one of the most found kidney disease. A great part (>99%) of circulating thyroid hormones were bound to proteins, thus derangements of blood proteins in nephrotic syndrome are potential to disturb thyroid hormones levels. This study was aimed to compare thyroid hormones levels changes in childhood Nephrotic Syndrome before and after remission.Method: Thirty four nephrotic syndrome patients studied on Department of pediatric of Dr. Kariadi Hospital, Semarang between April 1995 to June 1996 were for albumin, cholesterol, thyroid and thyroid stimulating hormone levels before and after remission and were tested with Wilcoxon signed rank test. The correlation between albumin and thyroxin levels before and after remission. were analyzed with Spearman correlation test.Results: T4 level before remission was 26.89±16.12 nmol/L, TSH 9.36±5.51 IU/ml, and after remission T4 106.63±28.02 nmol/L,TSH 1.78±1.91 μIU/mL. There were significant changes of thyroid hormones levels before and after remission (z=5.09; p=0.000). There were positive correlation between blood protein (albumin) level and thyroid hormone (T4) level in nephrotic syndrome before remission (r=0.51; p=0.000) and after remission (r=0.38; p=0.004). A great proportion of nephrotic syndrome patients, suffered from hypothyroidism and return to euthyroid after remission.Conclusions: Thyroid hormone levels changed during the course of nephrotic syndrome.Keyword : Thyroid hormone, TSH, T4, Nephrotic SyndromeABSTRAKLatar belakang : Sindroma nefrotik merupakan salah satu penyakit ginjal yang terbanyak ditemukan. Hormon tiroid beredar dalam darah berikatan dengan protein, sehingga pada gangguan kadar protein yang berat seperti pada sindroma nefrotik berpotensi mengganggu hormon tiroid. Penelitian ini bertujuan untuk mempelajari perubahan kadar hormon tiroid pada penderita sindroma nefrotik anak sebelum dan sesudah remisi.Metoda : Tiga puluh empat penderita sindroma nefrotik yang dirawat di Bagian Ilmu Kesehatan Anak RSUP Dr. Kariadi Semarang antara bulan April 1995 sampai Juni 1996 diperiksa perbedaan kadar albumin, kolesterol, tiroksin dan TSH sebelum dan sesudah remisi dan diuji dengan uji Wilcoxon signed rank test. Hubungan kadar albumin dan tiroksin pada sindroma nefrotik sebelum dan sesudah remisi di uji dengan uji korelasi Spearman.Hasil : Pada 34 penderita sindroma nefrotik sebelum remisi didapatkan rerata T4 26,89±16,12 nmol/L, TSH 9,36±5,51 IU/ml dan sesudah remisi didapatkan rerata T4 106,63±28,02 nmol/L, TSH rerata 1,78±1,91 μIU/mL. Ada perbedaan bermakna kadar hormon tiroid (T4) dan TSH sebelum dan sesudah remisi (z=5,09; p=0,000). Ada hubungan positif antara kadar albumin darah dengan kadar hormon tiroid darah T4 pada Sindroma nefrotik sebelum remisi (r=0,51; p=0,000) dan setelah remisi (r=0,38; p=0,004). Pada penderita sindroma nefrotik sebagian besar mengalami hipotiroidisme dan kembali euthiroid setelah remisi.Simpulan : Ada perubahan kadar hormon tiroid pada penderita Sindroma Nefrotik sebelum dan sesudah remisi.